Comparison and evaluation of analytic and diagnostic performances of four commercial kits for the detection of antibodies against Echinococcus granulosus and multilocularis in human sera. (July 2022) - Peruzzu, Angela; Mastrandrea, Scilla; Fancellu, Alessandro; Bonelli, Piero; Muehlethaler, Konrad; Masala, Giovanna; Santucciu, Cinzia
Abstract: Cystic echinococcosis (CE) is a disease caused by Echinococcus granulosus sensu lato (s.l.), an ubiquitous worldwide zoonotic agent affecting humans and animals. Diagnosis of CE in humans is usually performed by imagine techniques along with immunoassays. The aim of our study was to evaluate and compare four commercial diagnostic kits, based on the detection of IgG antibodies against E. granulosus and E. multilocularis . The study was performed on a total of 259 sera: the positive (n = 74) and the negative (n = 185) group. The following analytic and diagnostic performances of the four kits were evaluated: operator skills, specificity, sensitivity, repeatability, reproducibility, accuracy, positive and negative predictive values. Based on the parameters evaluated, all four tests demonstrated excellent quality and proved to be reliable diagnostic tools to support the clinical evaluation of human patients suspected of having CE. The four commercial assays, in our hands, presented altogether, a range of performances from good to excellent, being immunoblotting (IB) the most reliable, used as gold standard, followed by the immunochromatographic test (ICT) and finally the two enzyme linked immunosorbent assay (ELISAs). Highlights: Cystic echinococcosis is a severe zoonosis caused by Echinococcus granulosus sensu lato affecting humans and animals. Echinococcus granulosus sensu lato has an ubiquitous worldwide distribution. Improve the surveillance in hyperendemic areas for patients at risk of contracting CE. High consistency of immunoassay findings of reliable diagnostic tools is a valid support to the clinical evaluation.